Study of the mechanical properties of TRC-strengthened eccentric columns exposed to dry and wet cycles in a chloride salt erosion environment. (1st February 2020) - Shi-ping, Yin; Shi-chang, Li; Xun, Su; Xiang-qian, Hu
Highlights: TRC can be applied to enhance eccentric columns under the chloride salt erosion. Effect of environment, textile layers, reinforcement and chopped fibers are analyzed. The influence of chloride salt on the internal structure of TRC layer is explored. The bearing capacity formula of a TRC-strengthened eccentric column is obtained. Abstract: Reinforced concrete (RC) columns, which are important load-bearing components in building structures, located in the tidal zone of an actual project are generally subjected to eccentric loads. This paper explores the mechanical properties of textile-reinforced concrete (TRC)-strengthened eccentric columns in the tidal zone, and a total of 11 rectangular RC columns are included in the test. These tests consider the effects of the number of dry and wet cycles, the number of textile layers, the method of reinforcement (transverse and longitudinal) and the volumetric content of chopped fibers on the TRC strengthening effect. The results show that increasing the number of dry and wet cycles in a chloride salt environment will weaken the strengthening effect of the TRC. Moreover, the bearing capacity of the specimens increases as the number of TRC strengthening layers increases, but there is no obvious linear relationship between the two factors. Longitudinal TRC strengthening has a better overall effect than transverse TRC strengthening. The inclusion of chopped fibers in the TRC matrix will improve the development mode of surface cracks on the tension side of the concrete and increase the bearing capacity of the specimens. The effects of the number of dry and wet cycles and the volumetric content of chopped fibers on the internal microstructure of TRC are analyzed with the scanning electron microscopy (SEM) microtesting technique, and the mechanism of reinforcement degradation is explored from a microscopic view. Finally, by analyzing the bearing mechanism of the TRC-strengthened eccentric column and considering the TRC damage caused by the chloride salt erosion environment, a formula for the normal section bearing capacity of a TRC-strengthened eccentric column is obtained, and the calculated values have good consistency with the experimental values.